PENDIDIKAN ISLAM BAGI IBU RUMAH TANGGA PERSPEKTIF DEWI SARTIKA - Alaika M. Bagus Kurnia PS; Nur Ihsan Affandi; Fahmi Suryo Suryo (UIN Antasari Banjarmasin, 2022)
AbstractThis study aims to find out the actions and efforts of Dewi Sartika in improving the quality of education, especially for women. It can be said that the position of a woman as a potential housewife requires honing knowledge, skills, and additional work as expected by the figure of Dewi Sartika. The problem is that nowadays there are still prospective housewives who only have certain skills. And for work and other aspects it is still considered lacking. So this needs to be improved, especially for prospective housewives, namely in the aspects of education and skills. In this problem, the author uses qualitative methods in searching related data. The data taken can be in the form of relevant journals and books. The approach applied by Dewi Sartika in solving these problems is the strategic management approach which is supported by David Hanger's theory. Meanwhile, according to Dewi Sartika, women must be able to do everything in their lives, including serving their husbands, educating children, aspects of work, and so on.The attitude of persistence and fortitude possessed by Dewi Sartika in the world of education should be an example for us. As for the secluded book owned by Dewi Sartika entitled